X-ray diffraction has limited applicability in investigation of milk tampering. Issue 3 (6th August 2019) - Battaglini, Ana Paula Pavão; Urbano, Alexandre; Beloti, Vanerli; Rios, Edson Antonio; Ramos Pereira, Juliana; Fagnani, Rafael
Abstract: The aim of this work was to use X-ray diffraction to identify substances used for adulteration of raw milk and to determine if crystallographic analysis can detect extraneous substances in milk. Two unknown substances were sent anonymously by employers linked to the dairy chain, who claimed that they were added directly in milk prior to water addition by truck drivers. The samples were analyzed by X-ray diffraction and submitted to physicochemical analysis. The first substance was identified by X-ray diffraction as sodium citrate, complying with its physicochemical attributes, such as the powerful ability to decrease the freezing point. The second substance was identified by X-ray diffraction as sucrose and this result was also in agreement with its ability to increase the density, decrease the freezing point and finally, to be positive for sucrose in the resorcinol qualitative test. To evaluate if X-ray diffraction can detect extraneous substances already mixed in milk, fresh raw milk samples tampered with urea, sodium hydroxide, sodium citrate and sucrose were freeze dried and analyzed by X-ray diffraction, with no detection of any extraneous substances at any percentage. This is the first report of attempted diagnosis of extraneous substances in milk by X-ray diffraction. However, this technique can be useful only when applied to identify substances used for adulteration prior to its dilution in milk, since the amorphous nature of milk seems to be a limitation for the accurate detection of extraneous substances.